Dams in India-Nepal Border By Buddhi Narayan Shrestha - Thanju, Jeewan P (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
By Buddhi Narayan ShresthaKathmandu, Nepal: Bhumichitra; 1st Edition 2008; 408 pp.; NRs 440 (US $15)DOI: http://dx.doi.org/10.3126/hn.v8i0.4930 Hydro Nepal: Journal of Water, Energy and Environment Issue No. 8, 2011 January Page:  71-72 Uploaded date: 23 June, 2011